Historical and Thematic Appraisal of Persian Poetic Literature Produced by Syed Usman Harwani (1129-1220) - Muhammad Hassan; Asif Naveed; Anam Aziz; Rizwan Ullah Kokab (Social Science Review Archives, 2025)
This paper assesses the historical and thematic appraisal of Poetic Literature produced by an early Chishti Sufi Syed Usman Harwani and its impact on the audience during the poetic and Qawwali Mahafils of the Chishti Sufis. In this piece of research a qualitative analytical method is applied to highlight the contribution of the Sufi in form of his poetic Literature, as he contributed a lot to advance and reshape the contemporary environment through poetry which greatly influenced the audiences and left a deep impact on and gradual development of Persian and other native languages in the Sufi musical gatherings and Qawwali at the same time and touched the hearts of public in a peaceful manner and preached Islamic thoughts through lyrics. Among all Sufis of Indian Subcontinent, Syed Usman Harwani was the paragon of virtues and a leading Sufi in Indian context who guided spiritually the notable and men of letters. Especially Khawja Moeenuddin Chishti Ajmairi was among his disciples, who pioneered and advanced artistic threads in the field of poetry and music in subcontinent. The question that has been dealt in this research paper is that how the poetic literature of Chishti Sufis evolved among Chishti Sufis and their disciples, and signified and initiated the pinnacle time of the poetic excellence in subcontinent?